Critical cytoplasmic region of the interleukin 6 signal transducer gp130 is conserved in the cytokine receptor family. - Murakami, M (1991)
Interleukin 6 (IL-6) signal is transduced through gp130 that associates with a complex of IL-6 and IL-6 receptor. Truncations or amino acid substitutions offe introduced in the cytoplasmic region of human gp130, and the mutant cDNAs were transfected into murine interleukin 3-dependent cells to determine amino acid residues critical for generating the IL-6-mediated growth signal. In the 277-amino acid cytoplasmic region of gp130, a 61-amino acid region proximal to the transmembrane domain was sufficient for generating the growth signal. In this region, two short segments were significantly homologous with other cytokine-receptor family members. One segment is conserved in almost all members of the family, and the other is found especially in granulocyte colony-stimulating factor receptor, interleukin 2 receptor beta chain, erythropoietin receptor, KH97 (a granulocyte/macrophage colony-stimulating factor receptor-associated molecule), and interleukin 3 receptor. gp130 molecules with mutations in either of these two segments could not transduce growth signal. Loss of signal-transducing ability of gp130 with such a mutation coincided with disappearance of IL-6-induced tyrosine phosphorylation of gp130.